Preparation of Co-Amorphous Levofloxacin Systems for Pulmonary Application - Aljoscha Gabelmann; Claus-Michael Lehr; Holger Grohganz (MDPI AG, 2023)
Addressing antimicrobial resistance requires new approaches in various disciplines of pharmaceutical sciences. The fluoroquinolone levofloxacin (LEV) plays an important role in the therapy of lung infections. However, its effectiveness is limited by its severe side effects involving tendinopathy, muscle weakness and psychiatric disturbance. Therefore, there is a need for the development of an effective formulation of LEV with reduced systemic drug concentrations, thereby also reducing the consumption and excretion of antibiotics or metabolites. This study aimed for the development of a pulmonary-applicable LEV formulation. Co-amorphous LEV-L-arginine (ARG) particles were prepared by spray drying and characterised by scanning electron microscopy, modulated differential scanning calorimetry, X-ray powder diffraction, Fourier-transform infrared spectroscopy and next generation impactor analysis. Co-amorphous LEV-ARG salts were produced independently of varying process parameters. The use of 30% (v/v) ethanol as a solvent led to better aerodynamic properties compared to an aqueous solution. With a mass median aerodynamic diameter of just over 2 µm, a fine particle fraction of over 50% and an emitted dose of over 95%, the product was deemed suitable for a pulmonary application. The created process was robust towards the influence of temperature and feed rate, as changing these parameters did not have a significant influence on the critical quality attributes, indicating the feasibility of producing pulmonary-applicable co-amorphous particles for sustainable antibiotic therapy.